Investigating the heavy metal (Hg, Cd, Pb, Cr, As) binding affinity and sensing capability of 2-((2-(hydroxymethyl)quinolin-8-yl)oxy)-N-(quinolin-8-yl)acetamide - Li, Qianru; Jing, Shuting; He, Liping; Kong, Xianghe; Lan, Wenbo; Wang, Xiaofeng (Frontiers in Chemistry, 2025)
Addressing severe environmental and health threats posed by mercury, cadmium, lead, chromium, and arsenic (“five toxic” heavy metals), this study employs density functional theory (DFT) calculations and molecular simulations to investigate the capture and detection mechanisms of the dual-fluorescent probe 2-((2-(hydroxymethyl)quinolin-8-yl)oxy)-N-(quinolin-8-yl)acetamide in both water solvent and dimethyl sulfoxide (DMSO). Key findings indicate that the probe forms highly stable, planar complexes with arsenic, lead, and chromium, exhibiting significant red-shifts in UV absorption bands and enhanced fluorescence intensity–strongest for arsenic in water solvent, while arsenic/chromium complexes show markedly increased fluorescence in DMSO. This work demonstrates the probe’s selective recognition of As, Pb, and Cr, with solvent polarity modulating detection signals, providing a novel theoretical framework for monitoring and remediating heavy metal pollution.